The horse industry in Kansas - Conner, W. Archie (My University, 1906)
Introduction: The horse stands at the head of a noble tribe of quadrupeds, which naturalists term solepedes, or single hoofed, from having but one apparent toe, covered by a single integument of horn, although beneath the skin on each side are protuberances which may be regarded as rudimental toes. According to the view of modern geologists there is but one genus of the tribe, namely, equus, which comprehends six species according to Proffessor Low, of Edinburgh. EQUUS ASINUS - The ass. EQUUS ZEBRA - The zebra. EQUUS QUAGGA - The quagga. EQUUS BURCHELLII - The striped quagga. EQUUS HEMIONUS - The dziggithai. EQUUS CABALLUS - The common horse. Nature has not formed this powerful creature to shun the control of man, but has linked him by his natural wants and instincts to our society. It is only when under human guidance that his most useful faculties are exercised and his full maturity of strength and form attained. The horse is distinguished from all other equine genus by the superior expansion of the chest, the large development of his muscles, the greater strength and lateral distance of his limbs, the elevation of his withers, the long flowing hairs of his mane and tail and his loud and sonorous voice. At the age of two years he is able to propogate his race and at the age of five to seven has attained full maturity. The male, as is the same of other animals, is stronger and more courageous than the female. He is more difficult of subjugation but not less attached and generous. When deprived of his virile powers he approaches more to the character of the female.
Citation: Conner, W. Archie. The horse industry in Kansas. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Equine; Kansas; Animal Husbandry; Theses